Bible Translation of Non-Mandarin Han Fangyan (Dialects) in Mainland China: The Case of Swatow - Wong, Simon S. M. (The Bible translator, 2015)
This paper aims at raising awareness of the Bible translation needs among the non-Mandarin Han dialect groups in the People’s Republic of China, especially in the light of the recent reprinting of the 1898 Swatow New Testament by a Swatow Baptist Church in Hong Kong. Such needs are better understood in terms of the Chinese term fangyan, which means topolect (or, regionalect), rather than dialect; in particular, the non-Mandarin Han fangyan spoken in the southeast of the country, such as Cantonese (Yue), Hakka, Hokkien (Min), and so forth, are mutually incomprehensible. Bible translation work among the local fangyan remains very active in Taiwan. It is nevertheless not encouraged, if not forbidden, in Mainland China, mainly because of the country’s deliberate suppression of any fangyan publication. It is hoped that the 2001 revision of the language policy may give more room to the possibility of translation.